Faculty Service Loads and Gender: Are Women Taking Care of the Academic Family? - Cassandra M. Guarino; Victor M. H. Borden (Institute for the Study of Labor (IZA), 2016)
This paper investigates the amount of academic service performed by female versus male faculty. We use 2012 data from an online annual performance reporting system for tenured and tenure-track faculty at two campuses of a large public, Midwestern university as well as 2014 data from a large national survey of faculty at more than 140 institutions. We find evidence in both data sources that women faculty perform significantly more service than men, controlling for rank, race/ethnicity, and field or department. Our analyses suggest that the male-female differential is driven primarily by internal service – i.e., service to the university, campus, or department – rather than external service – i.e., service to the local, national, and international communities.
Keywords: I23; 330; faculty; gender